The role of CXCL12 axis in pancreatic cancer: New biomarkers and potential targets - Roberto, Michela; Arrivi, Giulia; Di Civita, Mattia Alberto; Barchiesi, Giacomo; Pilozzi, Emanuela; Marchetti, Paolo; Santini, Daniele; Mazzuca, Federica; Tomao, Silverio (Frontiers in Oncology, 2023)
Introduction Chemokines are small, secreted peptides involved in the mediation of the immune cell recruitment. Chemokines have been implicated in several diseases including autoimmune diseases, viral infections and also played a critical role in the genesis and development of several malignant tumors. CXCL12 is a homeostatic CXC chemokine involved in the process of proliferation, and tumor spread. Pancreatic ductal adenocarcinoma (PDAC) is one of the most aggressive tumors, that is still lacking effective therapies and with a dramatically poor prognosis. Method We conducted a scientific literature search on Pubmed and Google Scholar including retrospective, prospective studies and reviews focused on the current research elucidating the emerging role of CXCL12 and its receptors CXCR4 – CXCR7 in the pathogenesis of pancreatic cancer. Results Considering the mechanism of immunomodulation of the CXCL12-CXCR4-CXCR7 axis, as well as the potential interaction with the microenvironment in the PDAC, several combined therapeutic approaches have been studied and developed, to overcome the “cold” immunological setting of PDAC, like combining CXCL12 axis inhibitors with anti PD-1/PDL1 drugs. Conclusion Understanding the role of this chemokine’s axis in disease initiation and progression may provide the basis for developing new potential biomarkers as well as therapeutic targets for related pancreatic cancers.